A positioning solution method for roadheader under optical target occlusion conditions - WANG Pengpeng; LI Rui; LIU Xin; LI Xiang; FU Changliang (Gong-kuang zidonghua, 2024)
In order to solve the problem of interruption in the positioning of roadheader in the case that the optical target is blocked under the current commonly used integrated navigation positioning of roadheader based on 'inertial navigation+visual measurement+optical target', a positioning solution method for roadheader under optical target occlusion occlusion is proposed. Firstly, the method collects images of an optical target composed of four rectangular distributed target points in unblocked conditions, obtains the pixel coordinates of the imaging spot of the target points in the camera, and constructs a rectangle. Then, the method expands and constructs an auxiliary rectangular area box according to a certain proportion. Secondly, the method collects images of partially blocked target points, obtains the pixel coordinates of the imaging spot of the unblocked target points in the camera. The method determines the corresponding relationship between the unblocked target points and the imaging spot based on the Euclidean distance between the imaging spot of the target points and the vertex of the auxiliary rectangular area box, thereby determining the blocked target points. Thirdly, using the known geometric dimensions of the target and the target attitude information provided by inertial navigation, the method establishes the corresponding relationship between the projected target point and the imaging spot, and then solves for the pixel coordinates of the spot corresponding to the blocked target point. Finally, the spatial coordinates of the center position of the optical target are obtained using the perspective-N-point (PNP) algorithm to achieve the positioning solution of the roadheader. The experimental results show that when the optical target is blocked, by calculating the pixel coordinates of the light spot corresponding to the blocked target point, the problem of interruption in the positioning of the roadheader can be solved. It ensures the real-time positioning of the roadheader, and the positioning error meets the actual positioning requirements of the roadheader.